Plasma IL‐8 signature correlates with pain and depressive symptomatology in patients with burning mouth syndrome: Results from a pilot study. (11th December 2017) - Barry, Alison; O'Halloran, Ken D.; McKenna, Joseph P.; McCreary, Christine; Downer, Eric J.
Abstract : Background: Burning mouth syndrome (BMS) is a neuropathic orofacial pain condition of unknown aetiology that encompasses intra‐oral burning pain without abnormal clinical findings. Psychological, neural and inflammatory processes are associated with BMS pathogenesis. Currently, studies characterising plasma cytokine/chemokine profiles with pain and depression in patients with BMS are lacking. Considering that inflammation is associated with the pathophysiology of BMS, and that inflammation is closely associated with pain and depression, we aimed to correlate depressive symptomatology and oral cavity pain with plasma cytokine/chemokine signatures in a cohort of patients with BMS. Methods: In this study, plasma protein levels of Th1 cytokines (IFN‐γ, IL‐2, IL‐12p70, TNF‐α), Th2 cytokines (IL‐4, IL‐10, IL‐6, IL‐13) and the chemokine IL‐8 were assessed in patients with BMS (n = 10) and healthy volunteers (n = 10), using pro‐inflammatory‐10‐plex assays. Clinical histories, alongside self‐rated oral cavity pain intensities and depressive symptomatology were assessed using a visual analogue scale and the 16‐item Quick Inventory of Depressive Symptomatology questionnaires, respectively. Results: We present evidence that BMS is associated with increased depressive symptomatology and enhanced oral cavity pain. Plasma isolated from BMS patients display enhanced expression of the pro‐inflammatory chemokine IL‐8, when compared to plasma from healthy individuals. Plasma IL‐8 signature correlates with pain and depressive symptomatology in the study cohort. Conclusions: Overall, these findings indicate that plasma IL‐8 profiles are dysregulated in BMS and that modulation of IL‐8 production in the disorder may be a tool in the management of BMS symptomatology.